One novel curcumin derivative ZYX01 induces autophagy of human non-small lung cancer cells A549 through AMPK/ULK1/Beclin-1 signaling pathway - Zhou, Guang-Zhou; Wang, Qing-Qing; Wang, Peng-Bo; Wang, Zhi-Chen; Sun, Gang-Chun (Cellular and Molecular Biology, 2019)
Presently, curcumin derivatives had been paid more attention in view of their high bioavailability or water solubility, which herein possibly replaced the curcumin for their functional applications in future. Here, one novel chemically synthesized curcumin derivative, ZYX01, was used to identify anti-proliferation activity of human non-small lung cancer cells A549 and its anti-proliferative mechanism. Our study showed that ZYX01 could induce autophagic death of A549 cells by morphological observation, MTT assay, acridine orange staining and MDC assay, which possess a dose-and time-dependent manner. ZYX01-treated A549 cells possessed an increase in LC3-II/LC3-I ratio, upregulation of beclin-1 and downregulation of p62 expression. We further confirmed the cellular AMPK/ULK1/Beclin-1 signaling pathway in A549 cells after ZYX01 treatment. The anti-migration effect of ZYX01 in A549 cells was also explored by wound healing assay and transwell experiment. Current results had confirmed that ZYX01 induced A549 cells autophagy through AMPK/ULK1/Beclin-1 pathway and shed light on the future study on the anti-cancer molecular mechanism.